PENENTUAN BESARAN NISBAH BERDASARKAN SIMPANAN PADA PRODUK TABUNGAN BERENCANA DI BANK SYARIAH MANDIRI KCP BUAH BATU BANDUNG - Anggara, Ade Yuda; Radian, Aan (Al-Muamalat: Jurnal Ekonomi Syariah, 2019)
ABSTRACT Bank Syarih independently in fund raising offers savings plan products. This planning tabugan product using mudharabah mutlaqah contract, where the bank can manage customer funds and from the profit obtained dibagihasilkan between customers and banks in accordance with the percentage of the agreed ratio. In percentage ratio there is a difference with PBI No 10/14 / Dpbs 17 March 2008, where the ratio of the ratio is determined by both parties is not determined by unilateral by LKS (independent syariah bank) and not also based on nominal money deposited in the bank. The purpose of this research is to know: (1) the mechanism of savings product planning mudharabah mutlaqah in syariah bank mandiri KCP buah batu bandung (2) procedure of determination of ratio on savings product planning mudharabah mutlaqah in syariah bank mandiri KCP buah batu bandung (3) analysis of sharia economic law on savings products plan by using mudharabah mutlaqah contract in syariah bank standalone KCP buah batu bandung. The theory used in this research is mudharabah mutlaqah, the contract agreement between both parties shahibul maal and mudharib, where shahibul maal entrusted entirely to the funds invested to mudharib and shahibul maal does not provide limits of business type, time required, marketing strategy, as well as the business areas undertaken. The results of the research show that: (1) the planning savings mechanism is quite easy only by giving identity card in the form of KTP / SIM / Passport of the customer and having savings as the account of origin can already be the savings account of the planning (2) using mudharabah mutlaqah contract in BSM KCP of bandung stone is based on the average balance and will be booked into savings account of savers at next month, so that it can produce different nominal difference every month (3) analysis of this research shows there is different legal reference salaing PBS, fatwa and BSM, of which three have different laws in a planned savings product, the percentage ratio by virulence of DSN MUI NO 2 on savings, independent syariah bank may set its own percentage ratio, then an independent syariah using the ratio refers to the equivalent rate issued by Bank Indonesia or follow the fiscal policy, while in determining the Bank Indonesia ratio determined through PBI No 10/14 / Dpbs, stating the need for an agreement. The results of this study that the independent sharia bank KCP stone bandung allow to determine the percentage of the ratio unilaterally based on a stronger legal reference of the DSN MUI nowa No. 2 on savings.